The challenge of personal data protection in the era of digital economy - Kaļķe, Ilze (Riga Graduate School of Law, 2018)
The actual impact and effectiveness of the GDPR that comes into effect on May 25, 2018 will only be evident in the course of next years. Today, however it is crucial to understand how will the GDPR change the EU data protection playfield and if the new regulation is capable to address growing personal data and privacy challenges emerging from further digitalisation in the long term. The research question of this paper is: How capable and effective is the newly adopted EU data protection legislation to address the growing future privacy and data protection concerns associated with expansion of the Digital Economy?
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; General Data Protection Regulation (GDPR); Privacy